2014
DOI: 10.4322/rca.ao1461
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Spodoptera frugiperda in the wasteland of southern Pernambuco state, Brazil

Abstract: ABSTRACT:The fall armyworm (Spodoptera frugiperda) causes damage and reduction in maize production and is considered a pest difficult to control, thus determining its spatial distribution pattern contributes to the development of suitable sampling and control strategies. The aim of this study was to evaluate the spatial distribution of Spodoptera frugiperda in maize culture under the conditions of the wasteland of southern Pernambuco state. The experiment was conducted at the Experimental Station of Brejão -'I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
4
0
4
Order By: Relevance
“…To our knowledge, there are no results in the literature about the study of anisotropy for spatial point patterns in agriculture, for this reason it is not possible to make comparisons with other results. However, there are some works which analyze the clustering property of the S. frugiperda (e.g., Farias et al, 2008 andRios et al, 2014). We think that our results on clustering are in general coherent with those of Farias et al (2008) and Rios et al (2014), although in our study we did not take into account the size of the fall armyworm.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…To our knowledge, there are no results in the literature about the study of anisotropy for spatial point patterns in agriculture, for this reason it is not possible to make comparisons with other results. However, there are some works which analyze the clustering property of the S. frugiperda (e.g., Farias et al, 2008 andRios et al, 2014). We think that our results on clustering are in general coherent with those of Farias et al (2008) and Rios et al (2014), although in our study we did not take into account the size of the fall armyworm.…”
Section: Discussionmentioning
confidence: 50%
“…However, there are some works which analyze the clustering property of the S. frugiperda (e.g., Farias et al, 2008 andRios et al, 2014). We think that our results on clustering are in general coherent with those of Farias et al (2008) and Rios et al (2014), although in our study we did not take into account the size of the fall armyworm. In particular, Farias et al (2008) found that the spreading of the S. frugiperda for small larvae present aggregated behavior, and it becomes increasingly random with larval growth.…”
Section: Discussionmentioning
confidence: 50%
“…These results align with Hernández-Mendoza et al ( 2008): FAW lower den sities present an aggregated spatial distribution, while the higher densities have a random and uniform distribution. This trend does not occur in an absolute way since studies such as those by Ríos et al (2014) reported this aggregate dist ribution pattern, both for small and large fall armyworm larvae, both in early and advanced infestation stages.…”
Section: Spatial Estimationmentioning
confidence: 81%
“…Esse tipo de distribuição, também, foi encontrada por Silva et al (2011), Monteiro et al (2013) e Rios et al (2014) para diferentes pragas, culturas e localidades.…”
Section: Resultsunclassified
“…Os estudos da dependência espacial de pragas, por meio da geoestatística, têm sido bastante utilizados nos últimos anos, permitindo fazer um controle mais adequado dessas pragas (GREGO et al, 2006;SILVA et al, 2011;MONTEIRO et al, 2013;RIOS et al, 2014).…”
Section: Resultsunclassified